PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PASIEN DI WELLCLINIC GADING SERPONG - Anatha Pindika Putra Teguh; Sunaryo Oentara (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to analyze the effect of tangibility, reliability, assurance, empathy, and responsiveness on patient loyalty in the private healthcare sector. Data collection was carried out using online questionnaires for 200 outpatients that were receiving healthcare service in WellClinic Gading Serpong in June-August 2021 period with purposive sampling method. Data analysis was performed using Analisis partial least square-structural equation modelling (pls-sem), approach using SmartPLS software. The results show that all five dimensions in service quality had a positive effect on patient loyalty in WellClinic Gading Serpong, especially in Tangibility and Reliability. Contribution of this research was sent out idea to WellClinic Gading Serpong and similar private healthcare sector to improve aspect of service quality and which one dimension of service quality that they need more to improve to improve patient loyalty in WellClinic Gading Serpong for increment of total customer in Wellclinic Gading Serpong with expected healthcare service.